Legal Uncertainty In Fiduciary Guarantee Law: An Analysis Of Reality And Its Impact On Creditors - Utami, Putri Dwi; Lianti, Lita; Nadhilah, Fildzah Hanifati; Fauzi, Amanda Kirani (Diponegoro Private Law Review, 2021)
The existence of Law Number 42 of 1999 concerning Fiduciary Guarantees arises due to the urgency of the public who experience anxiety about collateral objects. This regulation addresses all fiduciary guarantees, but there is confusion and legal uncertainty in their implementation in the community. This can be seen from the concept and reality in the field that is not balanced. Therefore, the author will discuss this issue using normative legal research methods by taking a statutory and conceptual approach, as well as the formulation of the problem discussed, namely legal uncertainty in UUJF in juridical, normative, and sociological aspects to the impact on legal uncertainty, especially on creditors. This study aims to provide views and understanding of how such legal uncertainty occurs and its impact on the creditors concerned. The results of this study show that regulations regarding fiduciaries are still said to have not provided legal certainty for the Indonesian people, especially from creditors. Keywords: Fiduciary Guarantee, Creditor, Legal Certainty